KAJIAN EKSPERIMENTAL PENGARUH PENAMBAHAN SERAT KARUNG GONI UNTUK MEMPEROLEH HASIL KUAT LENTUR BALOK LAMINASI KAYU KRUING - WIKASNO, DANU; ULUL ALBAB, MUHAMMAD; SST., M.T., ANUNG SUWARNO; S.T., M.T., MARSUDI (Politeknik Negeri Semarang, 2016)
The development of increasingly rapid construction resulting in the need of building materials for the construction of buildings is increasing. A wooden one. To overcome this problem one way is the efficient use of wood that is in laminate. The need for special treatment to increase the strength of laminated wood beams with the provision of added material in the form of fiber sack. The purpose of this study is the use of wood waste kruing with thin dimensions as laminated wood beams, utilization of waste fiber jute sacks at the same influence on the flexural strength of wood laminated beams kruing, analyzing the flexural strength limit kruing laminated timber beams with the addition of fiber sack. The scope of the research that is being simulated laminate system is horizontal, the study is testing the flexural strength, the wood being simulated is kruing wood, the glue used is poly vinyl acetate (PVA). The test object is made with two variations A and B with a size of 5 cm x 10 cm x 100 cm. With A variation in the form of ordinary laminated beams without the addition of fiber while variation B in the form of laminated beams with the addition of fiber sack. From the results obtained flexural strength test of intact wooden beams kruing biggest is 807.240 kg/cm2 , the smallest is 657.930 kg/cm2 , and an average of 708.120 kg/cm2. Flexural strength of wood laminated beams kruing without additional fiber largest is 509.880 kg/cm2 , the smallest is 479.850 kg/cm2 and an average of 499.520 kg/cm2 . Flexural strength of wood laminated beams kruing with the addition of fiber jute sacks biggest is 444.150 kg/cm2 , the smallest is 390.810 kg/cm2 and an average of 418.950 kg/cm2 . The addition of fiber jute sacks againts wood laminated beams kruing results are not in accordance with the targets to be achieved and laminated beams can not be used for structural use.Kata kunci : laminate, wood kruing, burlap sacks.